PERAN PEREMPUAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA: TINJAUAN EKONOMI ISLAM - Fauzah, Nurmela; Fuad, Zaki; Farma, Junia; Umuri, Khairil (JURNAL MANAJEMEN DAKWAH, 2023)
This Along with the development of the times, women not only served as housewives but also played a role in helping the family's economy by working outside the home. This condition also occurs in Banda Aceh, with many women working as online motorcycle taxi drivers. So this study analyzes female workers who work as online motorcycle taxi drivers in the Koala community from an Islamic economic perspective. This study uses a qualitative approach with descriptive analysis in the form of field research (field research). The results found that the factors that influence women working as online motorcycle taxi drivers in the Koala community are caused by economic and sociocultural factors. The involvement of women in working as online motorcycle taxi drivers does not conflict with Islamic rules. Islam does not prohibit women from doing work outside the home, provided they do not violate the limits set by Islam. Economically, working as an online motorcycle taxi driver is very helpful for the family economy so that it can meet family needs. The government is expected to pay more attention to women workers so that they are comfortable and safe. Entrepreneurship training is also needed so that women are more independent and creative.